Aplikasi Statistik Perbandingan Sepak Bola Yang Bermain Di Champions League - Sofyan Mufti Prasetiyo; Deni Pratama Setia Budi; Risman Muhammad Hafidz; Melisa Dwi Hestiani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Football is the most popular sports game with a large number of fans highest in the world. be it small children, teenagers and adults who have the most competitive competitions between European clubs which are the center of football called the UEFA Champions League which contains 32 of Europe's best teams which are currently one of the shows that are in great demand by the world community. Match analysis is not only useful for increasing team competence, match analysis is also used by coaches to see the strengths of potential opponents, not only before the match but also during the match. Therefore, here we will try to make an application that contains important statistics that aim to be a prediction simulation for the UEFA Champions League matches. The type of research used by researchers is qualitative research with a descriptive approach. The results of the research conducted are in the form of applications that have a target market for people who like football with the aim of helping them predict the possibility of the outcome and running of a match that occurs in the UEFA Champions League based on the variable data that we have collected.